Christensen's physics of Diagnostic Radiology - Curry,Thomas S (Wolters Kluwer, 1990)
The fourth edition of this text provides a clear understanding of the physics principles essential to getting maximum diagnostic value from the full range of current and emerging imaging technologies. Updated material added in areas such as x ray generators (solid state devices), xerography (liquid toner), ct scanners (fast imaging technology) and ultrasound (color doppler).